Video documental sobre representaciones teatrales. - Rojas Flores, Daniela Andrea (2016)
The objective of this written work titled “Documentary Video regarding theatrical representations” is to realize and produce a communicational product of the group Los Perros Callejeros (The Street Dogs) with their play La Fiesta (The Party), whose characters are referents of Ecuador’s culture and artistic expression. The theoretical basis for this proposal is built on concepts around social sciences, culture, communication, and theater. Subtopics like popular culture, theatrical representations, amongst others, were derived from those concepts. The theater group Los Perros Callejeros transports the audience to a celebration in Quito’s streets. Its characters are taken out of the Andean party, where we find Mama Chuchumeca, Diablo Ocioso, Capariche, Danzante, and others, represented in different conventional and non-conventional settings. The street is the space that has afforded them freedom of expression, as well as a diverse and close audience.